Mapping TPACK Components in Implementing Edupreneur-Profiled Curriculum at Teacher Training and Education Institutions in Aceh - Lailatussaadah, Lailatussaadah; Hayati, Salma; Jamil, Asyraf Isyraqi Bin; Abdul Kadir, Fakhrul Adabi Bin (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
This research aims to explore the mapping of Technological Pedagogical Content Knowledge (TPACK) components of instructors in implementing the Edupreneur-profiled curriculum in Islamic Higher Education Institutions (PTKI) in Aceh. The researchers employed interview methods, observations, and document reviews involving three heads of study programs and six instructors from three PTKIs (Islamic Higher Education Institutions) in Aceh, namely UIN Ar-Raniry, IAIN Lhokseumawe, and STAIN Teungku Dirundang Meulaboh. The data analysis was conducted interactively. Instructors teaching Edupreneurship-profiled courses have successfully integrated Content Knowledge (CK), Pedagogical Knowledge (PK), Technological Knowledge (TK), Pedagogical Content Knowledge (PCK), Technological Pedagogical Knowledge (TCK), and Technological Content Knowledge (TPK) as components of TPACK in their teaching practices. This research contributes to mapping these components, thereby aiding instructors in effectively implementing the entrepreneurship-profiled curriculum. In conclusion, this research provides valuable insights into the effectiveness of Open Educational Resources (OER) on creative thinking within the context of science subjects, filling a notable gap in the existing literature and offering a foundation for further exploration in educational practices.